Employees’ Job Satisfaction on Accomplishing Routine Tasks: A Study of Programme Assistants in the Northern Provincial Council, Sri Lanka - Selvakumaran, K.; Wickeremasinghe, E.S.; Upananda, W.A. (University of Jaffna, 2012)
Job satisfaction describes feelings and attitudes of employees generate towards their jobs. The objective of this research study is to ascertain the levels of job satisfaction and analyzing the predictors of job satisfaction experienced amongst the programme assistants in the Northern Provincial Council (NPC). For the purpose, 137 programme assistants (N=137) were sampled by using stratified random sampling method. The questionnaire measures job satisfaction on six job facets in three dimensions, namely, extrinsic factors: pay, promotions, supervision; General factors: co workers, working condition, and Intrinsic factor: work itself. This study found that Programme Assistants of NPC were not satisfied with their jobs in key facets. Therefore Provincial Council should take measures to restructure promotion system, appropriate salary scale and providing other pay benefits. Further, NPC should consider improving working conditions, and nature of work.
Keywords: Factors affecting Job satisfaction; Job satisfaction; Northern Provincial Council of Sri Lanka; Programme Assistants